Long-term trends in the distribution of wealth and inheritance - James B. Davies; Rodrigo Lluberas; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2024)
This paper examines long-term trends in aggregate wealth and inheritance and in their distributions, focusing on developed economies. A key stylized fact is that wealth is less equally distributed than income. Financial assets predominate among the wealthy, while owner-occupied housing is crucial for middle groups, so higher stock prices raise wealth inequality while house price increases do the opposite. Inheritances exacerbate absolute wealth inequality but reduce relative inequality. Wealth inequality declined in advanced Western countries during the first half of the 20th century, then stabilized or rose. Aggregate wealth-to-income ratios have fluctuated, reflecting both market and policy influences, whereas inherited wealth proportions have declined over the long run. Continued increases in the value of employer-based pensions, housing and social security wealth in recent decades have acted to reduce wealth inequality, offsetting the disequalizing impact of financial asset price increases to a varying extent across countries.
Keywords: E01; H55; D15; D31; E21; G51; 330; Wealth; Inheritance; Inequality; Saving; History